American Useful Plants in Post-Medieval Europe: Integrating Archaeobotanical and Historical Evidence - J. Irmišová; M. Ballesteros; J. J. Garay-Vázquez; C. Moricca; J. Skružná; T. Majerovičová; L. Speleers; S. Preiss; M. Badura; J. Wiethold; O. Brinkkemper; J. P. V. Tereso; et al. (Ethnobotany and Economic Botany, 2026)
The arrival of Europeans in the Americas in 1492 initiated new transatlantic connections that, through colonial expansion and trade networks, brought useful plants to Europe. This study investigates archaeobotanical and historical evidence for the introduction of American plants to Europe from the late fifteenth to the twentieth century. We compiled 183 archaeobotanical records from 14 countries, representing 24 taxa from 11 botanical families. We examined which American plant species were introduced to Europe during the post-medieval period, and how their uses and significance varied across regions and social contexts. Archaeobotanical data indicate that early introductions occurred predominantly in elite secular and ecclesiastical settings across Europe. Historical sources identify Spain as the first entry point, though other European countries yielded more records. The large number of archaeobotanical finds in the Netherlands and at the Habsburg court in Prague reflects the current state of research, site coverage, preservation, and data accessibility. The significance of these plants in Europe was shaped by economic value, prestige, ritual use, and medicinal properties. Our study highlights the importance of integrating archaeobotanical and historical sources and provides the most comprehensive account to date of material evidence tracing the cultural trajectories of American plants in Europe.